2016
DOI: 10.1177/0011128716675359
|View full text |Cite
|
Sign up to set email alerts
|

Examining Specific Deterrence Effects on DWI Among Serious Offenders

Abstract: Deterrence research supports the idea that punishment curbs offending; however, results for the specific deterrent effects of drunk driving are more nuanced. This research is often limited in its use of non-offender samples, its failure to examine links between past sanctions and subsequent risk perceptions, and in its use of aggregate-level data, thereby precluding any exploration of individuals’ perceived sanction risks. The current study examines the relationship between 824 felony inmates’ experiences with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 51 publications
(71 reference statements)
0
4
0
Order By: Relevance
“…We also did not collect or assess whether individuals had a history of DWI or being stopped in suspicion of impaired driving. However, previous studies suggested prior DWI or impaired driving consequences have relatively little impact on related perceptions or behaviors (Bouffard et al, 2017; McCarthy et al, 2005). Although we were able to classify most individuals into either compensatory or non-compensatory strategy use, future research should consider additional decision strategies to reduce the number of unclassified individuals.…”
Section: Discussionmentioning
confidence: 91%
“…We also did not collect or assess whether individuals had a history of DWI or being stopped in suspicion of impaired driving. However, previous studies suggested prior DWI or impaired driving consequences have relatively little impact on related perceptions or behaviors (Bouffard et al, 2017; McCarthy et al, 2005). Although we were able to classify most individuals into either compensatory or non-compensatory strategy use, future research should consider additional decision strategies to reduce the number of unclassified individuals.…”
Section: Discussionmentioning
confidence: 91%
“…In the case of alcohol-related crashes, though rationality is affected by alcohol, a decision is being made. Not to cause harm but simply, perhaps to get home (see Bouffard & Exum, 2013; Bouffard, Niebuhr, & Exum, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This is especially true for drivers with very high alcohol levels for whom the external costs are higher, since such cases are more likely to lead to severe injuries or deaths. However, Bouffard, Niebuhr, and Exum [20] show that there is not always a deterrence effect of higher sentences for this type of crime. Other authors have expressed contrasting views about the effectiveness of prison sentences in the past.…”
Section: Introductionmentioning
confidence: 97%